Making Physics Reasoning Visible: A Narrative-Informed Design of Embedded Assessment in Collaborative Learning - Imam Permana; Misykat Malik Ibrahim; St. Syamsudduha; Ulfiani Rahman; Fitriani Kadir (International Journal of Educational Narratives, 2026)
Background. Collaborative physics learning can make classroom participation visible, yet the reasoning behind students’ answers often remains difficult to follow. This concern is especially relevant in teacher education, where pre-service physics teachers are expected to understand physical concepts and learn how explanations are formed, challenged, revised, and consolidated. Purpose. This study examined how embedded assessment within a collaborative digital learning trajectory made students’ reasoning visible during instruction on Simple Harmonic Motion. Method. A narrative-informed mixed-methods design account was used. Qualitative evidence was collected from digital worksheet responses, classroom observations, and student reflections, while quantitative learning outcome data served as supporting evidence. The learning sequence was organized into three episodes—ignition, cruise, and terminal—and was supported by a microsite and interactive digital worksheets. The analysis focused on how students’ written explanations, revisions, and reflections changed across these episodes. Results. The findings show that embedded assessment documented students’ initial intuitive ideas, captured conceptual negotiation during collaborative work, and preserved reflective consolidation after instruction. Students’ explanations gradually shifted from descriptive accounts of repeated motion toward more relational reasoning involving displacement, restoring force, velocity, acceleration, and equilibrium. Quantitative evidence also indicated improvement in conceptual understanding after initial ability was controlled, supporting the patterns found in the process data. Conclusion. Embedded assessment can function as narrative evidence of reasoning development when it is deliberately connected to collaborative tasks, digital documentation, and a coherent learning trajectory. This study offers a practical framework for using digital worksheets not only as task spaces, but also as tools for tracing, interpreting, and supporting reasoning development in collaborative physics teacher education.